08.10 Serum lipid and fatty acid profiles are altered in patients with polymyositis or dermatomyositis. (1st March 2017) - Raouf, Joan; Idborg, Helena; Olsson, Petter; Alexanderson, Helene; Dastmalchi, Maryam; Jakobsson, Per-Johan; Lundberg, Ingrid E; Korotkova, Marina
Abstract : Background: Polymyositis (PM) and dermatomyositis (DM) are chronic autoimmune diseases, characterised by muscle fatigue and low muscle endurance. Conventional treatment includes high doses of glucocorticoids and immunosuppressive drugs; however, few patients recover muscle function. We recently reported that immunosuppressive treatment affected the expression of genes related to lipid/fatty acid (FA) metabolism, suggesting altered lipid/FA-profiles in PM/DM patients. Objectives: To analyse lipid and FA profiles in sera from patients with polymyositis or dermatomyositis in comparison to healthy individuals and relation to immunosuppressive treatment. Methods: Serum samples were obtained from 13 patients with established PM or DM and 12 healthy individuals. The second cohort consisted of eight untreated patients diagnosed with definite PM or DM with available follow-up serum sample after eight months of immunosuppressive treatment. Functional Index 2 (muscle function) was assessed in the second cohort. Serum lipids were extracted by using liquid-liquid extraction. FA composition of total serum lipids was determined by gas chromatography provided with flame ionisation detector (GC-FID). FA composition of several lipid classes, e.g. triacylglycerols, phospholipids, sphingolipids, and lysophospholipids was analysed by using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: The FA composition of total serum lipids was altered in myositis patients compared to healthy individuals; the levels of C16:0 acid was significantly higher in myositis patients whereas the levels of C20:4 (n-6) acid was significantly lower. The levels of serum lipid species within phosphatidylcholine (PC), lysophosphatidylcholine (LPC) and triacylglycerol (TG) were significantly changed in myositis patients compared to healthy individuals. Immunosuppressive treatment resulted in increased levels of C20:2 (n-6) acid and C20:5 (n-3) acid as well as changed serum PC, PE and LPC profiles in myositis patients. Furthermore, a positive correlation was observed between the Functional index and the levels of PC(38:4) in serum from patients after treatment. Conclusions: FA composition of total serum lipids is altered in myositis patients compared to healthy controls. Immunosuppressive treatment resulted in changed FA composition of serum PC, PE, and LPC. These findings indicate that FA metabolism might be deregulated in PM and DM patients contributing to muscle inflammatory responses and loss of muscle function.